Planetary Passport : Re-presentation, Accountability and Re-Generation - McIntyre-Mills, Janet J. 1959- (Springer International Publishing, 2017)
This book explores the implications of knowing our place in the universe and recognising our hybridity. It is a series of self-reflections and essays drawing on many diverse ways of knowing. The book examines the complex ethical challenges of closing the wide gap in living standards between rich and poor people/communities. The notion of an ecological citizen is presented with a focus on protecting current and future generations. The idea is to track the distribution and redistribution of resources in the interests of social and environmental justice. The central argument looks for ways to hold the powerful to account so as to enable virtuous living by the majority to be demonstrated in what the author calls a "planetary passport"--A careful use of resources and a way to provide safe passage to those in need of safe habitat. The book argues that nation states need to find ways to control the super-rich through the governance process and to enhance a sense of shared ecological citizenship and responsibility for biodiversity. The fundamental approach is collaborative research. Planetary Passport: Representation, Accountability and Re-Generation is comprised of six chapters. Chapter 1 begins by making a case for a paradigm shift away from business as usual and the pursuit of profit at the expense of the social and environmental fabric of life. The aim is to explore alternatives and to discuss some ways of achieving wellbeing whilst the focus is on human rights, discrimination and outlining the notion of a planetary passport. Chapter 2 makes a specific link between people and the planet as a basis for understanding the nature of hybridity and interconnectedness and the implications for ethics. Chapter 3 focuses on building this planetary passport for social and environmental justice in order to enable people with complex needs to consider the consequences of either continuing to live the same way as before or making changes to the way that they live. Meanwhile Chapter 4 does the same as the previous chapter, but explores the political context of consumption and short term profit Chapter 5 examines the challenges and opportunities that come from explorations within a cross-cultural learning community. This includes a look at co-creation and co-determination. Finally Chapter 6 ends with a look to the future and a potential new framework for people and the planet through a planetary passport.
2.7.1 Vignette: Cartoonists at Charlie Hebdo.
Keywords: Economic development.; Cost and standard of living.; Business ethics.; Public administration.; Social change.; elektronické knihy; electronic books